Directors’ Board Control and Diversification Decision in Tunisian Companies - Gharbi, Manel; Jarboui, Anis (Asian Journal of Empirical Research, 2015)
The purpose of this paper is to identify the various indicators that are more likely to explain the corporate diversification decision. In addition, it examines the relationship between board composition and the diversification decision among the Tunisian firms. Our sampleis composed of 111 Tunisian companies studied over the period ranging between 2011 and 2013. Our findings reveal that the percentages of outside directors have positive and non-significant relationship with the diversification decision. Also our results confirm that there is negative and non-significant association persisting between ownership concentration and diversification.